Cardiovascular Toxicities of Small Molecule Tyrosine Kinase Inhibitors: An Opportunity for Systems‐Based Approaches. Issue 1 (26th November 2016) - Brown, S‐A; Nhola, L; Herrmann, J
Abstract : Once universally considered a rapidly fatal condition, cancer has increasingly become a chronic medical condition and comorbidities and adverse effects of cancer therapies have become increasingly significant. One of the leading advancements that has gained traction for the treatment of a variety of malignancies is the class of small molecule tyrosine kinase inhibitors (TKIs). Although, in many aspects revolutionary, TKIs have their own profile of side effects, including cardiovascular side effects, the most common being hypertension (HTN), congestive heart failure, corrected QT (QTc) prolongation, and instances of premature coronary heart disease. Herein, we describe the mechanisms of small TKI‐induced cardiovascular toxicity and related intracellular signaling. In particular, systems‐based approaches to the understanding of small TKI‐induced cardiovascular toxicity are addressed. The pathophysiology of synergic cardiovascular toxicity from TKIs, anthracyclines, and monoclonal antibodies (e.g., trastuzumab, bevacizumab) is illustrated. Finally, recommendations are made for implementing systems medicine in clinical practice, for individualized cardiovascular wellness after cancer therapy.